2002
DOI: 10.1051/kmae:2002074
|View full text |Cite
|
Sign up to set email alerts
|

Roundtable Session 2b: National Interactions Between Non-Indigenous and Indigenous Crayfish Species

Abstract: The main object of the present essay is to summarise some aspects underlying the interactions between non-indigenous (NICS) and indigenous (ICS) crayfish species. The discussion has been also extended to the effects exercised by NICS on the natural habitats they occupy. While doing research on the dyads NICS/ICS, one starting point is to extrapolate common traits that make NICS good invaders from the analysis of their biology, ecology and ethology and the comparison with indigenous species. A subsequent step i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…Higher SMR in P. leniusculus compared to A. pallipes is indeed consistent with known differences in life history traits between the species such as higher growth rates in P. leniusculus (Guan & Wiles, 1999), higher predatory functional response (Haddaway et al, 2012), and dominance during interspecific interactions (Holdich et al, 1995). Such life-history traits are also frequently cited explanations for the invasive capabilities of P. leniusculus, and other invasive crayfish (Gherardi et al, 2002;Gherardi & Daniels, 2004;Pintor & Sih, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Higher SMR in P. leniusculus compared to A. pallipes is indeed consistent with known differences in life history traits between the species such as higher growth rates in P. leniusculus (Guan & Wiles, 1999), higher predatory functional response (Haddaway et al, 2012), and dominance during interspecific interactions (Holdich et al, 1995). Such life-history traits are also frequently cited explanations for the invasive capabilities of P. leniusculus, and other invasive crayfish (Gherardi et al, 2002;Gherardi & Daniels, 2004;Pintor & Sih, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the species is listed in the EU Directive 92/43/EEC, commonly known as Habitat Directive (Annex II and V) and it is also listed as endangered by the IUCN (Füreder et al, 2010). Moreover, the cause of disappearance of many freshwater crayfish populations is linked (Gherardi and Holdich, 1999;Gherardi et al, 2002) to the introduction of non-indigenous species, such as Procambarus clarkii (Girard, 1852) and Orconectes limosus (Rafinesque, 1817), carriers of the oomycete Aphanomyces astaci Schikora 1906, the crayfish plague (Aquiloni et al, 2011). Recent studies in its native habitat showed that P. clarkii has distinct ecological requirements with respect to A. pallipes (Dorr and Scalici, 2013) and the propagule pressure drives the colonization success of invasive freshwater crayfish (Capinha et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The replacement of A. pallipes by NICs may be due to crayfish plague, or in a few cases by competition (if the NICs are not carrying crayfish plague), or because A. pallipes had already been lost due to degradation of habitat, which was later colonised by NICs. Although indigenous and non-indigenous crayfish do not live in syntopy, there is a risk of transmission of crayfish plague between sites by the movement of birds, fish, and fishermen's equipment, carrying spores through the territory (Gherardi et al, 2002). The introduction of NICs is a major threat to indigenous crayfish stock, but it appears that A. pallipes started to decrease in the 1970s.…”
Section: Discussionmentioning
confidence: 99%